2019
DOI: 10.1213/ane.0000000000003759
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-Care Ultrasound Abnormalities in Late-Onset Severe Preeclampsia: Prevalence and Association With Serum Albumin and Brain Natriuretic Peptide

Abstract: BACKGROUND: Pilot studies applying point-of-care ultrasound (POCUS) in preeclampsia indicate the presence of pulmonary interstitial edema, cerebral edema, and cardiac dysfunction. Laboratory markers of oncotic pressure (albumin) and cardiac dysfunction (brain natriuretic peptide [BNP]) may be abnormal, but the clinical application remains unclear. We investigated the prevalence of pulmonary interstitial syndrome (PIS), cardiac dysfunction, and increased optic nerve sheath diameter (ONSD) in late-on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 38 publications
0
6
1
4
Order By: Relevance
“…The alterations in the ONSD indicate a state of cerebral edema as a part of generalized edema, fluid overload and serves as a predictor of volume status in women with severe preeclampsia (31) . Three studies (15,19,20) demonstrated ONSD levels before delivery in preeclampsia, and one study evaluated ONSD before and after delivery in parturients with severe preeclampsia and found that ONSD was lower significantly at 24 hours after delivery compared to predelivery values.. In addition, they found a significant correlation between ECS and ONSD measurements both before and after delivery (15) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The alterations in the ONSD indicate a state of cerebral edema as a part of generalized edema, fluid overload and serves as a predictor of volume status in women with severe preeclampsia (31) . Three studies (15,19,20) demonstrated ONSD levels before delivery in preeclampsia, and one study evaluated ONSD before and after delivery in parturients with severe preeclampsia and found that ONSD was lower significantly at 24 hours after delivery compared to predelivery values.. In addition, they found a significant correlation between ECS and ONSD measurements both before and after delivery (15) .…”
Section: Discussionmentioning
confidence: 99%
“…Pachtman et al (18) demonstrated that women with severe preeclampsia had B-lines measured before delivery more frequently than women without severe features. Another 2 studies were able to detect B-patterns by LUS before delivery (indicating pulmonary interstitial syndrome) in women with severe preeclampsia (19,20) .…”
Section: Discussionmentioning
confidence: 99%
“…The POCUS helped narrow the differential rapidly and facilitate immediate treatment. There has been support for POCUS examination of the lungs, heart, and optic nerve sheath diameter to help detect the presence of pulmonary interstitial edema, cerebral edema, and/or cardiac dysfunction while managing patients with pre-eclampsia and eclampsia [13]. Some managing critically ill pregnant women suggest opportunities for further use of multiorgan POCUS including transcranial Doppler and transcranial color-coded duplex sonography which are not traditionally done in the ED setting [14].…”
Section: Discussionmentioning
confidence: 99%
“…In their study, B-lines were detected in 5 parturients of 20, giving an incidence of 25%. 27 In another study, Ortner et al 28 described a high proportion of pre-eclamptic patients (24%) with pulmonary interstitial syndrome in their cohort of 95 pre-eclamptic patients. We found a remarkably higher incidence, 64.3%, than in previous studies, 27,28 whereas the lower incidence reported by Zieleskiewicz et al 27 may have been due to their smaller sample size.…”
Section: Anesthesia and Analgesiamentioning
confidence: 97%
“…27 In another study, Ortner et al 28 described a high proportion of pre-eclamptic patients (24%) with pulmonary interstitial syndrome in their cohort of 95 pre-eclamptic patients. We found a remarkably higher incidence, 64.3%, than in previous studies, 27,28 whereas the lower incidence reported by Zieleskiewicz et al 27 may have been due to their smaller sample size. Ortner et al 28 enrolled women with late-onset pre-eclampsia as a large cohort of 95 pre-eclamptic women.…”
Section: Anesthesia and Analgesiamentioning
confidence: 97%